2018
DOI: 10.15766/mep_2374-8265.10772
|View full text |Cite
|
Sign up to set email alerts
|

Let's Talk About Sex: The Social Determinants of Sexual and Reproductive Health for Second-Year Medical Students

Abstract: IntroductionSexual health is influenced by a myriad of social factors including health care access, social and cultural norms, insurance status, educational level and health literacy, economic status, sex, gender identity, and sexual orientation and behavior. It is pivotal to educate future physicians about these social determinants so that they can work to mitigate the resulting disparities and thereby improve the health of patients and their communities.MethodsThis 2-hour, large-group session for second-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…This is an important intervention, as research with MSM couples in which both partners are HIV-negative has shown low interest in PrEP given perceptions of low HIV risk, even in the setting of condomless sex with partners outside of the relationship [83]. Of the published resources for medical education regarding sexual health, all are focused on patients presenting without their sexual partner [84][85][86][87][88][89]. This indicates an opportunity for development of training materials, including standardized patient encounters including both a patient and their sexual partner for couples-based HIV riskreduction counseling training.…”
Section: Discussionmentioning
confidence: 99%
“…This is an important intervention, as research with MSM couples in which both partners are HIV-negative has shown low interest in PrEP given perceptions of low HIV risk, even in the setting of condomless sex with partners outside of the relationship [83]. Of the published resources for medical education regarding sexual health, all are focused on patients presenting without their sexual partner [84][85][86][87][88][89]. This indicates an opportunity for development of training materials, including standardized patient encounters including both a patient and their sexual partner for couples-based HIV riskreduction counseling training.…”
Section: Discussionmentioning
confidence: 99%
“…Panel discussions are an effective method for humanizing illnesses and diseases, as well as exposing medical students to real-life consequences of the social determinants of health, particularly sexual and reproductive health [11]. Exposure to diverse speaker opinions (i.e.…”
Section: Preferred Modality Of Instructionmentioning
confidence: 99%
“…MedEdPORTAL has published curricula related to structural racism and racial disparities in health, 13 , 14 LGBTQ health, 15 , 16 and social determinants of health, 17 including social determinants of sexual and reproductive health. 18 However, these curricula do not explicitly center on the principles of RJ.…”
Section: Introductionmentioning
confidence: 99%